Small business management : entrepreneurship and beyond - Hatten, Timothy S. (Houghton Mifflin Co., 2006)
Hatten provides a balanced introduction to both entrepreneurship and small business management before turning his focus toward achieving and maintaining a sustainable competitive advantage as a small organization. Current issues including global opportunities, service, quality and technology are highlighted throughout the text, and the Third Edition features an increased emphasis on small business ownership by women and minority groups